Efinaconazole in the treatment of onychomycosis - Lipner SR; Scher RK (Infection and Drug Resistance, 2015)
Shari R Lipner, Richard K Scher Department of Dermatology, Weill Cornell Medical College, New York, NY, USA Abstract: Efinaconazole 10% topical solution is a new triazole recently approved for the treatment of onychomycosis. It inhibits fungal lanosterol 14α-demethylase in the ergosterol biosynthesis pathway, has potent antifungal activity against dermatophytes, as well as activity against Candida spp. and non-dermatophyte molds, and showed promising results in clinical trials. This review summarizes the mechanism of action, in vitro and in vivo data, clinical trials, safety, and quality-of-life data of efinaconazole as it applies to the treatment of onychomycosis. Keywords: efinaconazole, Jublia, onychomycosis, fungal infection, nail infection